The Oxford handbook of public policy - Moran, Michael (Oxford Oxford University Press, 2006)
Public policy is the business end of political science. It is where theory meets practice in the pursuit of the public good. Political scientists approach public policy in myriad ways. Some approach the policy process descriptively, asking how the need for public intervention comes to be perceived, a policy response formulated, enacted, implemented, and, all too often, subverted, perverted, altered, or abandoned. Others approach public policy more prescriptively, offering politically-informed suggestions for how normatively valued goals can and should be pursued, either through particular policies or through alternative processes for making policy. Some offer their advice from the Olympian heights of detached academic observers, others as 'engaged scholars' cum advocates, while still others seek to instill more reflective attitudes among policy practitioners themselves toward their own practices. The Oxford Handbook of Public Policy mines all these traditions, using an innovative structure that responds to the very latest scholarship. Its chapters touch upon institutional and historical sources and analytical methods, how policy is made, how it is evaluated and how it is constrained. In these ways, the Handbook shows how the combined wisdom of political science as a whole can be brought to bear on political attempts to improve the human condition.
Includes bibliographical references and indexes.
Keywords: Policy sciences